The Association between Chronic Obstructive Pulmonary Disease and Coronary Artery Disease in Patients Undergoing Coronary Angiography. (2nd January 2019) - Hong, Yongzhe; Graham, Michelle M.; Southern, Danielle; McMurtry, Michael Sean
Abstract: Chronic obstructive pulmonary disease (COPD) and coronary artery disease (CAD) are leading causes of morbidity and mortality. There are conflicting results regarding the association between COPD and CAD. We sought to measure the association between COPD and angiographically diagnosed CAD in a population-based cohort. We performed a retrospective analysis using data from the Alberta Provincial Project for Outcomes Assessment in Coronary Heart Disease (APPROACH), a prospectively collected registry capturing all patients undergoing coronary angiography in Alberta, Canada, since 1995. We included adult patients who had undergone coronary angiogram between April 1, 2007 and March 31, 2014. CAD was present if at least one coronary artery had a significant stenosis ≥50%. COPD was present if the patient had a documented COPD history and was prescribed bronchodilators or inhaled steroids. We evaluated the association between COPD and CAD using univariable and multivariable logistic regression. There were 26, 137 patients included with a mean age of 63.3 ± 12.2 years, and 19, 542 (74.8%) were male. The crude odds ratio (OR) of having CAD was 0.83 (95% CI 0.74–0.92) for patients with COPD compared to those without COPD. The adjusted OR was 0.75 (95% CI 0.67–0.84) after controlling for age, sex, smoking history, body mass index, hypertension, diabetes, hyperlipidemia, peripheral artery disease and cardiac family history. In patients undergoing coronary angiography, COPD was negatively associated with CAD with and without the adjustment for classic risk factors. COPD patients should be properly examined for heart disease to reduce premature mortality.